Ghulam Mohammad: His Life & Work - Mansoor Akbar Kundi (Journal of Political Studies, 2016)
The rule of Ghulam Mohammad as the Governor General of Pakistan (1951- 55) is one of the controversial, authoritarian and undemocratic chapter of the Pakistan politics. He was a man behind the gun which laid rest to two important Ministries in East Pakistan and at center, and dissolved the Constituent Assembly which was to frame the future constitution of the country. It had already done the home work and was to present the final draft. He was a member of Constituent Assembly, Finance Minister whom Quaid-e-Azam called “My Financial Wizard”. He was a successful Finance Minister, Master-planner and politically a man with undemocratic and unconstitutional mind. During his rule the seeds of military praetorian and bureaucratic rule were sown.